Assessing The Effect of Non-Surgical Periodontal Therapy on Levels of Caspase 3 And 7 in Patients With Chronic And Aggressive Periodontitis - A Systematic Review Protocol - Baliga, Vidya; Baliga, Sudhindra; Dhadse, Prasad; Oza, Ranu; Sharma, Varsha; Nazli Khatib, Mahalaqua (International Journal of Psychosocial Rehabilitation, 2020)
Background: Chronic periodontitis (CP) and Aggressive Periodontitis (AgP), are characterized by destruction of periodontal tissues in response to dental plaque. Both have localized and generalized presentations initiated by bacterial plaque, but they differ in the pattern of destruction; familial aggregation and the quantity of dental plaque. Apoptosis has been reported to be one of the mechanisms of tissue destruction in periodontitis, and a family of cysteine proteases, named caspases have been reported to mediate the process. Two mechanisms involved in apoptosis are intrinsic and caspase-dependent extrinsic pathways. These pathway results in the formation of a death-inducing signaling complex (DISC) which in turn causes activation of the executioner caspases-3,6&7 to start the process of cell-death or apoptosis. In subjects with chronic periodontitis, the probability of detection of Caspase-3 has been found to be greater in gingival crevicular fluid compared to serum and saliva. Additionally, detection of caspase-3&7 marked an early event prior to any overt morphological changes characteristic of apoptosis. Therefore, evaluation of Caspase levels may help in early detection of sites with periodontitis as well as probably determine the probability of an inactive site becoming active. Therefore, compositional changes in gingival crevicular fluid of site specific periodontal disease may help in correlating the level of disease activity and tissue destruction.Objectives: To assess the effect of non-surgical periodontal therapy on levels of caspase 3 and 7 in patients with chronic and aggressive periodontitis. Search Methods: We will search PUBMED and CENTRAL, EMBASE without language restrictions up to March 2019. We will also search for ongoing studies in trial registers, perform handsearching, check bibliographic references of relevant articles to seek potentially relevant research. We won’t apply any restrictions on language, date, or publication status. Selection Criteria: We will include randomised controlled (parallel-group or cross-over) trials, case control studies, cohort studies, case reports comparing the levels of caspase3 and 7 before and after SRP in patients with AgP and CP.